Patient attitudes and preferences for the management of pregnancy of unknown location - Jessica K. Wu, B.S; Emily N. Sadecki, M.D; Moira A. Kyweluk, Ph.D., M.P.H; Suneeta Senapati, M.D., M.S.C.E; Anne N. Flynn, M.D; Elizabeth Steider, M.B.E; Tracey Thomas, M.P.H; Kurt T. Barnhart, M.D., M.S.C.E (Elsevier, 2022)
Objective: To understand patient attitudes and preferences when faced with the uncertainty of pregnancy of unknown location (PUL). Design: Qualitative, interview-based study. Setting: University Hosptial. Patient(s): Patients aged >18 years sampled from the emergency department and a subspecialty fertility practice of a university hospital system. Intervention(s): Six to 8 weeks after resolution of a PUL, with an ultimate clinical outcome of either an intrauterine pregnancy, spontaneous abortion, or ectopic pregnancy. Participants underwent either surgical, medical, or expectant management. Main Outcome Measure(s): Thematic analysis of the virtual, semistructured interviews (45-60 minutes in length) conducted with participants to identify commonly expressed priorities was performed. Result(s): Interviews were completed from October 2020 to March 2021 until thematic saturation was achieved (n = 15). Resolution diagnoses included intrauterine pregnancy (26.7%, n = 4), ectopic pregnancy (40.0%, (n = 6), and spontaneous abortion (33.3%, n = 5). Moreover, 66.7% (n = 10) of the patients presented to the emergency department, whereas 33.3% (n = 5) presented to a subspecialty fertility clinic. All had desired pregnancies. Thematic analyses revealed 4 related priorities around PUL management: health of pregnancy; health of self; future fertility; and diagnostic prediction and diagnostic certainty. The relative balance of these priorities was dynamic and evolved throughout the course of management with different outcomes. A second set of themes related to logistical preferences included mental health support, clarity of treatment and next steps, and continuity of care. Interrater reliability was validated with a pooled κ of >0.8. Limitations include that all participants had desired pregnancies, and the experiences of those who experienced different pregnancy outcomes may have been affected by recall bias. Conclusion(s): These data demonstrate novel themes around related priorities in patients with desired pregnancies diagnosed with a PUL previously underappreciated by clinicians. The balance of these priorities evolved throughout management with increasing information and clarity. Continually reevaluating relevant patient priorities and preferences is essential to the comprehensive management of PUL.